Complement functional tests for monitoring eculizumab treatment in patients with atypical hemolytic uremic syndrome. (16th July 2014) - Cugno, M.; Gualtierotti, R.; Possenti, I.; Testa, S.; Tel, F.; Griffini, S.; Grovetti, E.; Tedeschi, S.; Salardi, S.; Cresseri, D.; Messa, P.; Ardissino, G.
Summary Background Atypical hemolytic uremic syndrome (aHUS) is a thrombotic microangiopathy characterized by hemolysis, platelet consumption, and renal injury. Eculizumab, a mAb that blocks complement activity, has been successfully used in aHUS. Objectives To optimize eculizumab therapy in aHUS patients by monitoring complement functional tests and markers of disease activity. Patients/Methods We studied 18 patients with aHUS (10 males; eight females; age range, 2–40 years) treated with eculizumab to induce and/or maintain disease remission. Patients were followed up for a cumulative observation period of 160 months, during which blood samples were obtained at various time intervals to measure complement activity (Wieslab for the classical, alternative and mannose‐binding lectin complement pathways) and the parameters of disease activity (haptoglobin and lactate dehydrogenase serum levels, and platelet count). The intravenous eculizumab doses of 12–33 mg kg−1 were initially administered every week, with the interval between doses being gradually extended to 2 weeks, 3 weeks and 4 weeks on the basis of strict laboratory and clinical control. Results Complement activity was normal before eculizumab treatment, regardless of the state of the disease (activity or remission). It was completely suppressed 1 week, 2 weeks and 3 weeks after the last eculizumab infusion (mean values ± standard deviation: 1% ± 1% to 3% ± 5% for both the classical and alternative pathways; P = 0.0001 vs. baseline), and partially suppressed after 4 weeks (22% ± 26% and 16% ± 27%; P = 0.0001 vs. baseline). The increase in the time interval between eculizumab infusions did not change disease activity markers. Conclusions Monitoring complement tests can allow a safe reduction in the frequency of eculizumab administration in aHUS while keeping the disease in remission.